THE CONCEPT OF HYBRID MANUFACTURING FOR HIGH PERFORMANCE PARTS# - Boivie, K.; Karlsen, R.; Ystgaard, P. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: The development of additive manufacturing technology (AMT) for metallic materials has reached a level where the processes are capable of producing complex geometries with industrial grade material properties. However, AMT is still hardly competitive with conventional (subtractive) machining with regard to production speed, accuracy, and surface quality. To address these limitations, AMT can be combined with subtractive manufacturing technology into a hybrid manufacturing system. This paper introduces the concept of hybrid manufacturing with examples from ongoing industrial case studies, and describes the requirements for the future development of an integrated hybrid manufacturing system. AFRIKAANSE OPSOMMING: Die ontwikkeling van byvoegende vervaardigingstegnologie vir metaal het die peil bereik waar prosesse in staat is om komplekse meetkundes te vervaardig met nywerheidsgraad materiale. Die tegnologie ondervind egter strawwe mededinging vanaf konvensionele masjinering ten opsigte van produksienetheid, akkuraatheid en oppervlakte-afwerking. Die twee mededingende metodes kan egter tesame gebruik word as